2017
DOI: 10.2174/1874944501710010090
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Risk Factors of Cardiometabolic Disease Among Female University Students in Riyadh, Saudi Arabia

Abstract: Background:Prevalence of cardiometabolic diseases (CMD), especially among the youth, is a growing public health concern in both developed and developing countries. Objective:To examine cardiovascular and metabolic disease risk factors among a cohort of female university students in Riyadh, Saudi Arabia. Method:Two hundred and twenty-three (223) female students aged 17-25 years participated in the study. Both physical and physiological parameters were assessed using standard procedures and equipment. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…24,25 A study in Saudi Arabia of 223 female university students showed that 8.5% were obese and 22.4% were overweight. 26 Another study investigating the risk factors of coronary heart disease among 214 medical students in Saudi Arabia showed that 18.9% of males and 10.6% of females were obese. 27 A study in Colombia which investigated cardiovascular and diabetes risk factors in 450 medical students showed that only 10% of the whole sample was overweight.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 A study in Saudi Arabia of 223 female university students showed that 8.5% were obese and 22.4% were overweight. 26 Another study investigating the risk factors of coronary heart disease among 214 medical students in Saudi Arabia showed that 18.9% of males and 10.6% of females were obese. 27 A study in Colombia which investigated cardiovascular and diabetes risk factors in 450 medical students showed that only 10% of the whole sample was overweight.…”
Section: Discussionmentioning
confidence: 99%